KAREKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK MIE JAGUNGPADA RASIO PATI JAGUNG DENGAN TEPUNG TERIGU - A. Lanyala, Ilham; Rahim, Abdul; Samudin, Sakka (AGROTEKBIS, 2018)
Noodles is one of the most popular carbohydrate-rich food products in Indonesia which is often used as an alternative staplefood.Noodle products have been produced using wheat flour as its their main raw material. However, some of it can be substituted with corn starch as it can provide very high nutrient content such as carbohydrates,etc. The objective of this research was to determine the optimal formulation of dry noodle made from mixture of corn starch andwheat flourwhich has good physicochemical characteristic in various ratios and to determine the level of panelist acceptance to the dry noodle organoleptic properties.The noodles were analyzed for their water content,ash content,swelling power,cooking loss, water holding capacity (WHC) and oil holding capacity (OHC), and organoleptic properties (color, flavor, taste).This study used a Completely Randomize design with the treatments were the formulation ratio of corn starch and wheat flour i.e. 100:0; 90:10; 80:20; 70:30; 60:40; 50:50;40:60 and 30:70.The results of this study indicated that WHC, OHC, swelling power , cooking loss, moisture content, and ash content of the dry corn noodles tended to increase with the decrease of corn starch, but the value of the sensory properties test data has a tendency to increase as the corn starch reduced. Themixture of corn starch and wheat at the ratio of 40: 60 resulted in the most optimal physicochemical characteristics as well as the most preferred noodle by the panelists.